Comparison and Applications of Multiplying Two 3 by 3 Matrices - Gao, Shanzhen; Gao, Weizheng; Malomo, Olumide; Allagan, Julian D.; Eyob, Ephrem; Su, Jianning (2023 Congress in Computer Science, Computer Engineering, & Applied Computing (CSCE), 2023)
Multiplying matrices can be very challenging although it seems straightforward. Many researchers have studied the multiplication of two 3 by 3 matrices by using Strassen Algorithm in the past 50 years. They focused on the complexity from the mathematical and algorithmic points of view. We will discuss the processing time comparison from a practical point of view in Python IDLE, Jupyter Notebook, and Colab. Several open problems are posted to challenge our readers.